A year in perspective: The impact of the COVID‐19 pandemic on engagement with Jigsaw youth mental health services. Issue 7 (22nd November 2021) - Rossouw, Johannes; Carey, Eleanor; Doyle, Elizabeth; O'Brien, Gillian; Cullinan, Sarah; O'Reilly, Aileen
Abstract: Aim: The COVID‐19 pandemic has presented significant challenges for young people and youth mental health services. To address a gap in knowledge about the impact of the pandemic and associated restrictions on youth mental health services, this paper examined the nature of young people's engagement with Jigsaw's brief intervention service during the pandemic. Method: Data gathered from young people engaging with Jigsaw's brief intervention service in the 12 months after the official declaration of the COVID‐19 pandemic ( n  = 6161), and 12 months prior ( n  = 8665) were examined. Results: There were less referrals to Jigsaw during the pandemic, especially during lockdown periods, but this rebounded when public health restrictions were eased. A higher proportion of females ( p  < .001) and 12–17 year olds ( p  < .001) were referred during the pandemic period. There was an increase in the proportion of young people who presented with anxiety ( p  < .001) and sleep changes ( p  < .001). Although 12–16 year olds reported significantly higher levels of distress during the pandemic ( p  < .05), the effect size was small. Young people reported high levels of satisfaction with the new phone/video modes of support offered by Jigsaw, and the overall attendance rate improved during the pandemic period. Conclusions: The impact of COVID‐19 on young people's mental health needs to be considered as a priority. This paper is helpful for services considering the long‐term mental health needs of young people, and the best way of meeting those needs.